2015
DOI: 10.1093/mmy/myv088
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic analyses of Calcineurin A subunit inArthroderma vanbreuseghemii

Abstract: Calcineurin is a serine/threonine protein phosphatase that consists of catalytic (calcineurin A) and regulatory (calcineurin B) subunits. The conserved protein plays important roles in various biological processes. Drug combination of fluconazole and the calcineurin inhibitor (FK506) showed synergistic effects against dermatophytes. In the current study, we identified the calcineurin A homologous gene (TmcanA) in the dermatophyte Arthroderma vanbreuseghemii (anamorph: Trichophyton mentagrophytes). Knockdown mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Calcineurin has both general and specific roles in different organisms. In some fungi, the calcineurin catalytic subunit is an essential gene, including in A. nidulans, where it plays a role in growth arrest at an early stage of the cell cycle (Alshahni et al, 2016;Prokisch et al, 1997;Rasmussen et al, 1994;Viaud et al, 2003). However, in most fungi, the deletion or knockdown of the calcineurin catalytic subunit results in defective hyphal morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin has both general and specific roles in different organisms. In some fungi, the calcineurin catalytic subunit is an essential gene, including in A. nidulans, where it plays a role in growth arrest at an early stage of the cell cycle (Alshahni et al, 2016;Prokisch et al, 1997;Rasmussen et al, 1994;Viaud et al, 2003). However, in most fungi, the deletion or knockdown of the calcineurin catalytic subunit results in defective hyphal morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions between the components of protein kinase C, high-osmolarity glycerol (HOG) and calcineurin pathways have been observed to regulate chitin and glucan synthesis (Cervantes-Chavez et al, 2011;Juvvadi and Steinbach, 2015;Munro et al, 2007). Interestingly, calcineurin also interacts with the components of the HOG pathway to regulate the synthesis of secondary metabolites, as shown in Arthroderma vanbreuseghemii, where calcineurin A affects the production of a yellow pigment under hyperosmotic conditions (Alshahni et al, 2016). In our study, the DcnaA strain secreted a yellow pigment into the agar medium that was not observed for the WT strain.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal hydrophobins, in general, play an important role in the growth and development of most fungi [ 19 ]. Thus, both biotic and abiotic environmental conditions have been proven to affect the expression of hydrophobin genes and various signaling pathways such as cAMP/PKA, Ca 2+ /calmodulin, MAPK, and the cell cycle have been identified as regulatory pathways for fungal hydrophobin expression [ 20 21 22 23 24 ]. Among these, MAPK signaling pathways are particularly promising.…”
mentioning
confidence: 99%
“…For example, calcineurin-defective fungal strains exhibit reduced formation of asexual spores and sexual structures and cannot complete the morphogenic transition (i.e., yeast to hypha and vice versa) (Cao et al, 2014;Choi et al, 2009;Huang et al, 2015;Juvvadi and Steinbach, 2015;Lee et al, 2013). The calcineurin signaling pathway also controls host-pathogen interactions in both fungi and protists, such as the hydrophobicity of spores, host cell receptor engagement, actin depolymerization, and cell invasion (Alshahni et al, 2016;Paul et al, 2015;Philip and Waters, 2015). In summary, calcineurin is involved in virulence via multiple mechanisms, which we discuss in more detail below.…”
Section: Functions Of the Ca 2+ -Calcineurin Signaling Pathway In Eukaryotic Pathogensmentioning
confidence: 99%
“…In Mucor circinelloides, one of the key Mucorales responsible for mucormycosis, calcineurin coordinates the yeast-hyphal dimorphic transition and fungal spore size, which are crucial processes that contribute to virulence (Lee et al, 2013) and alter host-pathogen interactions (phagosome maturation and host cell death) (Lee et al, 2015). In Trichophyton mentagrophytes (Arthroderma vanbreuseghemii), a dermatophyte species that causes skin and nail infections in animals and humans, calcineurin is also involved in hyphal morphogenesis, thermal stress resistance, and spore hydrophobicity (Alshahni et al, 2016). Importantly, calcineurin inhibitors in combination with other antifungal agents against T. mentagrophytes and Mucorales showed synergistic effects, suggesting that calcineurin is an attractive antifungal target (Shirazi and Kontoyiannis, 2013).…”
Section: Functions Of the Ca 2+ -Calcineurin Signaling Pathway In Eukaryotic Pathogensmentioning
confidence: 99%